Thought Leadership and Women's Liberation Politics - Janae Knott (Caribbean Studies Students' Union, 2022)
Claudia Jones' life and intellectual work have made impactful contributions in several spaces, including Marxist-Leninist ideology and anti-imperialism discourse. This review analyzes The Left of Karl Marx: The Political Life of Black Communist Claudia Jones written by Carol Boyce Davies. Davies offers valuable insight into Jones' anti-imperialist ideas, which are layered as she believed imperialism was the root cause of racism and fascism. Further- more, Davies draws upon a wide range of Jones' journalistic pieces to highlight the impact she has had in areas like Communist ideology and women's political liberation.